Pendampingan Layanan Zakat Menggunakan Sistem Informasi Arus Keuangan Masjid pada Dewan Kemakmuran Masjid - Effendi, Diana; Dhaniawaty, Rani Puspita; Fitriawati, Mia; Cancerina, Delviola; Nugraha, Ramdan (ADMA : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Managing zakat services using a financial flow information system in accordance with technological developments can help the mosque prosperity council (DKM) to be more effective in recording and distributing zakat. The aim of this Community Service (PKM) is to open the insight and awareness of DKM Nurul Huda administrators, that the application of information technology (IT) can be carried out in religious organizations. Currently DKM Nurul Huda processes payments and distribution of zakat using handwriting. This makes it difficult for Ziswaf officers to calculate the amount of zakat that must be paid by muzakki and makes it difficult to record mustahik when distributing zakat. This PKM helps utilize SiKeMas (Mosque Financial Flow Information System) in managing zakat fitrah, trade and income. SiKeMas is an application built to make it easier for DKM administrators to manage mosque financial flows. One of the modules in SiKeMas is the receipt and distribution of zakat. The method for implementing this PKM is Service Learning. The results achieved from this service are participants' increasing insight regarding the application of IT in religious organizations. DKM Nurul Huda installed SiKeMas on the mosque's inventory computer. This change was also measured from the participant satisfaction questionnaire with this PKM activity, where the index value of 99% stated that participants were helped and found it easy to use SiKeMas in carrying out its functions and duties serving muzakki and mustahik.